EFEKTIVITAS PENERAPAN METODE PENUGASAN BERBASIS PORTOFOLIO DALAM PEMBELAJARAN GAMBAR TEKNIK PROGRAM KEAHLIAN TEKNOLOGI KONSTRUKSI DAN PROPERTI SMK NEGER 2 BOGOR - Tanisha Gusach Veritza, - (2021)
The rapid spread of COVID-19 and its impact for human health, has caused the government in Indonesia to impose Large-Scale Social Restrictions (LSSR) and the Enforcement of Restrictions on Community Activities (ERCA). Schools as places of learning for students are given rules to not impose face-to-face learning and are replaced to online learning  at each student's home. In Engineering Drawing subjects, essential  aspects that must be achieved by students are knowledge, skills, and attitudes. In accordance with the core competencies and aspects of achievement in the Engineering Drawing subject, a portfolio-based assignment method is given whose contents are a pile of student work. This study aims to see how the effectiveness of portfolio-based assignments on the achievements that must be obtained in the subject of Engineering Drawing class X TKP for the school year of 2020/2021 at SMK Negeri 2 Bogor. This research was conducted by reviewing the learning process and student learning outcomes during one school year. The results of this study shows low effectiveness of the teaching materials used in the student learning process and task assessment, while the learning process of the materials and the given portfolio-based assignments are quite effective. On learning outcomes, referenced by the minimum score criteria of Engineering Drawing subject, students' average score is pretty good. With a percentage of 89% of students have passed the minimum score criteria so that student learning outcomes are still categorized as effective portfolio-based assignments in learning Engineering Drawing. Keywords: effectiveness, engineering drawing, assignment, portfolio